Innovative approaches to enhancing crack repair: Performance optimization of biopolymer-infused CXT - Asvitha Valli, Sankaranarayanan; Ravi Kumar, Muthuswamy Saraswathi (High temperature materials and processes, 2024)
Biopolymer-modified cementitious repair material (CXT) is a composite material designed to enhance the properties of traditional cementitious materials through the incorporation of biopolymers. CXT is formed by blending cement (C) with biopolymers such as xanthan gum (XG) and additives like tartaric acid (TA), which improve the material’s performance characteristics. This study investigates the effects of varying dosages of XG, TA contents, and curing durations on the performance characteristics of CXT. We evaluated key performance indicators, including the flowability, workability, setting time, compressive strength, and shrinkage. The optimal formulation XG 1:2 TA0.6 achieved a maximum compressive strength of 25 N·mm ² and a flexural strength of 9.4 N·mm ², with negligible shrinkage. The results showed rapid early strength development, with the material reaching over 77% of its final compressive strength within the first 14 days. These findings highlight the potential of CXT for crack-repair applications, offering improved workability, accelerated setting times, and reduced environmental impact compared to traditional repair materials. This study provides valuable insights for optimizing the formulation of CXT for enhanced performance in real-world applications.